2009
DOI: 10.1002/cmdc.200900180
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of New Antagonists of Bacterial Quorum Sensing in Vibrio harveyi

Abstract: Bacterial quorum sensing has received much attention in recent years because of its relevance to pathological events such as biofilm formation. Based on the structures of two lead inhibitors (IC50: 35-55 microM) against autoinducer-2-mediated quorum sensing identified through virtual screening, we synthesized 39 analogues and examined their inhibitory activities. Twelve of these new analogues showed equal or better inhibitory activities than the lead inhibitors. The best compound showed an IC50 value of approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 50 publications
0
31
0
1
Order By: Relevance
“…In Helicobacter pylori (a gastric pathogen), SFN inhibits urease activity, which generates ammonia and thus neutralizes gastric acidity and promotes inflammation (Fahey et al, 2013). Recently, a number of sulfur-containing compounds have been employed as a new class of QS inhibitors, including ajoene from garlic extract (with disulfide and sulfinyl groups) (Jakobsen et al, 2012b) and sulfur-containing molecules that were found to inhibit the AI-2 QS system of Vibrio harveyi (Li et al, 2008;Peng et al, 2009). Similarly, ITCs have also been found to display QS-inhibiting activity.…”
Section: Inhibition Of Enzymic or Regulatory (Quorum Sensing Qs) Actmentioning
confidence: 99%
“…In Helicobacter pylori (a gastric pathogen), SFN inhibits urease activity, which generates ammonia and thus neutralizes gastric acidity and promotes inflammation (Fahey et al, 2013). Recently, a number of sulfur-containing compounds have been employed as a new class of QS inhibitors, including ajoene from garlic extract (with disulfide and sulfinyl groups) (Jakobsen et al, 2012b) and sulfur-containing molecules that were found to inhibit the AI-2 QS system of Vibrio harveyi (Li et al, 2008;Peng et al, 2009). Similarly, ITCs have also been found to display QS-inhibiting activity.…”
Section: Inhibition Of Enzymic or Regulatory (Quorum Sensing Qs) Actmentioning
confidence: 99%
“…It is interesting that sulfur-containing compounds appear to be a new class of molecules capable of inhibiting QS (3, 5). Li et al (40) found two sulfur-containing compounds from an in silico-based virtual screening to target the AI-2 QS system from Vibrio harveyi, and several analogues were identified to exert bioactivity (52). These molecules contain a sulfone group, in contrast to ajoene, which contains disulfide and sulfinyl groups.…”
Section: Figmentioning
confidence: 99%
“…With the concept of molecular mimicking and the goal of identifying antagonist of AI-2 receptor proteins, Wang and co-workers found a few sulphone compounds using highthroughput virtual screening able to antagonise LuxP receptor in V. harveyi (Peng et al 2009;Ni et al 2008a). The authors suggested the key role of the sulphone group of these compounds in the interaction with the LuxP receptor.…”
Section: Targeting Ai-2 Receptorsmentioning
confidence: 96%